The Role of Digital Technologies in the Education System - Umarova Fotima Abdurahimovna (Newinera Publisher, 2020)
The purpose of this article is to analyze the introduction and use of information and communication technologies (ICT) in the special disciplines of higher education, to teach teachers how to improve the effectiveness of teaching and learning through information and communication technologies. This article discusses the issues of improving the knowledge and skills of students through the use of modern information and communication technologies in the preparation of specialists, increasing students' interest in the educational process and the ability to apply their knowledge in practice in the future. The focus is on the need to develop appropriate strategies for a new educational role and, in addition, to enhance the role of learners in integrating information and communication technologies into the educational process. The role and perspective of the teachers was very important, highlighting them as key players in the process. The data show that there is a belief that the use of information and communication technologies in the educational process will help increase the effectiveness of education and facilitate the organization of the educational process. In particular, it shows that the contribution of information and communication technologies to the improvement of the educational process in educational institutions, where information and communication technologies is an innovative factor, is high. Achieving this high level means that the educational institution must not only modernize technological means, but also change the models of teaching.